BNIP3 promotes HIF‐1α‐driven melanoma growth by curbing intracellular iron homeostasis. (1st May 2021) - Vara‐Pérez, Mónica; Rossi, Matteo; Van den Haute, Chris; Maes, Hannelore; Sassano, Maria Livia; Venkataramani, Vivek; Michalke, Bernhard; Romano, Erminia; Rillaerts, Kristine; Garg, Abhishek D; Schepkens, Corentin; Bosisio, Francesca M; et al.
Abstract: BNIP3 is a mitophagy receptor with context‐dependent roles in cancer, but whether and how it modulates melanoma growth in vivo remains unknown. Here, we found that elevated BNIP3 levels correlated with poorer melanoma patient's survival and depletion of BNIP3 in B16‐F10 melanoma cells compromised tumor growth in vivo . BNIP3 depletion halted mitophagy and enforced a PHD2‐mediated downregulation of HIF‐1α and its glycolytic program both in vitro and in vivo . Mechanistically, we found that BNIP3‐deprived melanoma cells displayed increased intracellular iron levels caused by heightened NCOA4‐mediated ferritinophagy, which fostered PHD2‐mediated HIF‐1α destabilization. These effects were not phenocopied by ATG5 or NIX silencing. Restoring HIF‐1α levels in BNIP3‐depleted melanoma cells rescued their metabolic phenotype and tumor growth in vivo, but did not affect NCOA4 turnover, underscoring that these BNIP3 effects are not secondary to HIF‐1α. These results unravel an unexpected role of BNIP3 as upstream regulator of the pro‐tumorigenic HIF‐1α glycolytic program in melanoma cells. Synopsis: This cancer signalling study reports a pro‐tumorigenic role for mitophagy receptor BNIP3 in melanoma, mitigating intracellular iron levels and controlling activity of prolyl hydroxylase PHD2. This feedforward loop favors HIF‐1α‐driven glycolytic phenotypes and tumor growth. High BNIP3 expression in melanoma patients correlates with poor survival. BNIP3 deficiency in mice reduces melanoma growth. BNIP3‐depleted melanoma cells show reduced HIF‐1α protein levels, glycolysis defects and exacerbated lysosomal turnover of the ferritinophagy receptor NCOA4. Elevated intracellular iron in BNIP3‐deprived cells promotes PHD2‐mediated degradation of HIF‐1α. A HIF‐1α hydroxylation‐mutant rescues tumor growth potential of BNIP3‐silenced cells. Abstract : Mitophagy receptor BNIP3 facilitates skin cancer by supporting HIF1‐1α protein stability.